Role of mothers in preventing tuberculosis in children: A scoping review - Aja, Nursia; Karsidi, Ravik; Anantanyu, Sapja; Lestari, Anik (Narra J, 2024)
Tuberculosis (TB) remains a significant global health challenge, especially for children. The aim of this scoping review was to investigate the role of mothers in preventing childhood TB transmission and highlight effective strategies and associated barriers. A systematic literature search was conducted using PubMed, Web of Science, and Scopus, covering articles up to January 17, 2024. The search included keywords like “mother,” “parents,” “care,” “prevention,” and “tuberculosis.” Eligibility criteria included peer-reviewed articles on maternal health interventions for TB prevention in children and published in English. The study selection process involved screening titles and abstracts, followed by full-text reviews by Rayyan Artificial Intelligence (AI). Eighteen studies were analyzed, revealing the crucial roles of mothers and healthcare workers in TB prevention. The results indicated that in South Africa, only 47% of eligible pregnant women underwent Mantoux testing, with lower rates in rural areas. The isoniazid preventive therapy (IPT) uptake rate was 79%, with geographical variations. Barriers included insufficient patient information, inadequate screening facilities, and healthcare providers' knowledge gaps. Parental involvement, particularly by mothers, is vital for adherence to TB preventive measures. Challenges in integrating TB case-finding with antenatal care and prevention of mother-to-child transmission (PMTCT) services included inconsistent screening and healthcare worker shortages. Enhancing health services, reducing stigma, and integrating TB prevention into existing programs are essential. In conclusion, this review underscores that effective childhood TB prevention requires a coordinated approach that incorporates the efforts of the mother and healthcare worker. Addressing barriers such as contact tracing gaps and diagnostic delays, alongside enhancing maternal health education and support, is essential for improving TB prevention and management. Targeted interventions and collaborative efforts are needed to reduce transmission and improve health outcomes, particularly in bridging rural-urban disparities.